HUBUNGAN PENGETAHUAN SUAMI TENTANG PERUBAHAN FISIOLOGIS DAN PSIKOLOGIS IBU HAMIL DENGAN DUKUNGAN SUAMI DI JORONG SURAU BATU NAGARI SUNGAI PUA TAHUN 2016 - Fransiska, Mellia; Yulia, Yulia (Jurnal Kesehatan - STIKes Prima Nusantara, 2018)
Breast cancer was a malignant disease due to the growth of abnormal cells in the breast can come from the mammary gland or supporting tissues such as fat and nerves. Based on Record Medical observation in Achmad Mochtar Hospital patients age ≥ 45 years who were breast cancer 2015-2016 as many as 372 people. The study aims to determine the risk factors of breast cancer incidence in elderly women. Research method of analytic study with the case-control approach, conducted in Poly Surgery and Inpatient Surgery Room Achmad Mochtar Hospital. Case population was elderly suffering from breast cancer recorded in data Record medical year 2016 counted 61 people. The samples were 42 (21 cases + 21 controls). The results of bivariate analysis of risk factors for breast cancer incidence in elderly women were family history (OR = 15) menarche age (OR = 8.5), and hormonal hormone use (OR = 15,438). family history, the age of menarche and the use of hormonal KB was a risk factor for breast cancer incidence and statistically, there was a significant relationship. It was suggested to the Hospital to provide counseling and counseling to female patients who checked themselves to Poly Surgery on the importance of breast cancer prevention efforts.